Epidemiological study of rubella outbreaks in Rajasthan, India - Garg, Rajesh; Singh, Kamaljit (International Journal Of Community Medicine And Public Health, 2017)
Background: Rubella is one of the major causes of significant morbidity and congenital deformities in India. Rubella immunization is yet to be formally introduced in National Immunization schedule across the country. Strong surveillance system for rubella is the key for prevention and control of congenital rubella syndrome. The outbreaks of rubella in Rajasthan in 2014 were investigated. The objective was to study the socio demographic profile of rubella outbreak in Rajasthan Methods: The data of the AFP cum measles and rubella surveillance project of Rajasthan was used for analysis. This is an analytical, cross sectional study where 2 districts of Rajasthan having confirmed rubella outbreak in 2014 were included. A total of 101 laboratory plus epidemiologically linked rubella cases were considered. Statistical analysis: Percentages, proportions and Chi square test were applied. Results: In three outbreaks, 101 cases were of rubella (laboratory confirmed + epidemiologically confirmed). Maximum numbers (around 53%) of cases were from the age group 1-4 years and 54.5% male child. The disease starts in early age (4 months) and affected up to the age group of 27 years. Conclusions: There was an outbreak of rubella cases in one district and mixed outbreak in second one. Currently rubella vaccination coverage is zero. Considering the currently available knowledge and reports, it is well justified that CRS can be controlled by effective immunization program and inclusion of rubella vaccination in the national immunization program of India is much awaited. Rubella vaccination is a cost effective measure and it can very easily piggy back Measles vaccine.